2013
DOI: 10.3390/molecules18022150
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles and Water- and Fat-Soluble Precursors of Saanen Goat and Cross Suffolk Lamb Flavour

Abstract: This paper evaluates the concentrations of water- and fat-soluble precursors of meat flavour, with the aim of characterising the effect of species on the volatile profile of grilled goat and lamb meat. Compared to goat, lamb meat had higher levels of saturated fatty acids—SFA, monounsaturated fatty acids—MUFA and polyunsaturated fatty acids—PUFA and similar levels of sugars and free amino acids, except for lysine and glycine, which were higher in goat. Major differences were detected in lipid-derived volatiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…(Z) ‐4‐Heptenal derives from linolenic acid (C18:3 n‐3 ) and has been correlated with lamb flavor in previous studies (Elmore et al., ), while (E) ‐2‐nonenal and 2‐heptanone derive from C18:2 n‐6 (Elmore et al., ). The decreased RA of 2‐ethyl‐3,6‐dimethylpyrazine with age ( P ≤0.05) and the absence of a positive correlation with the other pyrazines in the (older) April lambs; Figure ) could be related to decreased levels of free amino acids (for example, cysteine, glycine) that promote their formation (Madruga, Dantas, Queiroz, Brasil, & Ishihara, ) or a decrease in body protein content and synthesis in sheep with age (9 mo compared with 13 mo of age) (Lobley, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Z) ‐4‐Heptenal derives from linolenic acid (C18:3 n‐3 ) and has been correlated with lamb flavor in previous studies (Elmore et al., ), while (E) ‐2‐nonenal and 2‐heptanone derive from C18:2 n‐6 (Elmore et al., ). The decreased RA of 2‐ethyl‐3,6‐dimethylpyrazine with age ( P ≤0.05) and the absence of a positive correlation with the other pyrazines in the (older) April lambs; Figure ) could be related to decreased levels of free amino acids (for example, cysteine, glycine) that promote their formation (Madruga, Dantas, Queiroz, Brasil, & Ishihara, ) or a decrease in body protein content and synthesis in sheep with age (9 mo compared with 13 mo of age) (Lobley, ).…”
Section: Resultsmentioning
confidence: 99%
“…(); (19) Giri, Osako, Okamoto, and Ohshima (); (20) Göğüş, Özel, and Lewis (); (21) Kochhar (); (22) Kondjoyan and Berdagué (); (23) Madruga et al. (); (24) Madruga et al. (); (25) Poehlmann and Schieberle (); (26) Rapisarda et al.…”
Section: Methodsmentioning
confidence: 99%
“…However, other criteria in relationship with total fat content in meat must be considered when intensity of odour and flavour of meat is evaluated. In fact, Madruga et al (2013) reported that high total fat content from lambs is associated with a higher intensity of flavour compared with goats because it has a higher concentration of volatile compounds derived from lipids, mainly saturated lipids. In our study, Ch lambs showed higher fatness scores (see Sañudo et al, 2012).…”
Section: Fatty Acid Profile Of Intramuscular and Kidney Knob Fatmentioning
confidence: 99%
“…ese findings indicate that postmortem ageing promoted the release of FAAs. Madruga et al [27] studied the water-soluble amino was increased with prolonged aging so that taste characteristics would be abundant in the cooked meat.…”
Section: Differential Characteristic Metabolitesmentioning
confidence: 99%